Optimal Design of Power System Stabilizer In Bakaru Power Plant Using Bat Algorithm - Muhammad Ruswandi Djalal; Muhammad Yusuf Yunus; Herman Nawir; Andi Imran (Muhammadiyah University, Sidoarjo, 2017)
The problem of using Power System Stabilizer (PSS) in generator excitation is how to determine optimal PSS parameter. To overcome these problems, the authors use a method of intelligent bats based algorithm to design PSS. Bat Algorithm is an algorithm that works based on bat behavior in search of food source. Correlation with this research is, food sources sought by bats represent as PSS parameters to be optimized. Bat's algorithm will work based on a specified destination function, namely Integral Time Absolute Error (ITAE). In this research will be seen the deviation of velocity and rotor angle of each generator, in case of disturbance in bakaru generator. The analysis results show that the uncontrolled system produces a large overshoot oscillation, and after the addition of PSS oscillation control equipment can be muted. So that the overshoot and settling time of each generator can be reduced and the generator can quickly go to steady state condition.